Z-Selective Olefin Metathesis on Peptides: Investigation of Side-Chain Influence, Preorganization, and Guidelines in Substrate Selection - Mangold, Shane L. (American Chemical Society, 2014)
[Image: see text] Olefin metathesis has emerged as a promising strategy for modulating the stability and activity of biologically relevant compounds; however, the ability to control olefin geometry in the product remains a challenge. Recent advances in the design of cyclometalated ruthenium catalysts has led to new strategies for achieving such control with high fidelity and Z selectivity, but the scope and limitations of these catalysts on substrates bearing multiple functionalities, including peptides, remained unexplored. Herein, we report an assessment of various factors that contribute to both productive and nonproductive Z-selective metathesis on peptides. The influence of sterics, side-chain identity, and preorganization through peptide secondary structure are explored by homodimerization, cross metathesis, and ring-closing metathesis. Our results indicate that the amino acid side chain and identity of the olefin profoundly influence the activity of cyclometalated ruthenium catalysts in Z-selective metathesis. The criteria set forth for achieving high conversion and Z selectivity are highlighted by cross metathesis and ring-closing metathesis on diverse peptide substrates. The principles outlined in this report are important not only for expanding the scope of Z-selective olefin metathesis to peptides but also for applying stereoselective olefin metathesis in general synthetic endeavors.